The Effects of 120 Minutes of Simulated Match Play on Indices of Acid-Base Balance in Professional Academy Soccer Players. Issue 6 (June 2016) - Harper, Liam D.; Clifford, Tom; Briggs, Marc A.; McNamee, Ged; West, Daniel J.; Stevenson, Emma; Russell, Mark
Abstract : Abstract: Harper, LD, Clifford, T, Briggs, MA, McNamee, G, West, DJ, Stevenson, E, and Russell, M. The effects of 120 minutes of simulated match play on indices of acid-base balance in professional academy soccer players. J Strength Cond Res 30(6): 1517–1524, 2016—This study investigated the changes in indices of acid-base balance during 120 minutes of simulated soccer match play that included a 30 minute extra-time (ET) period. Eight English Premier League academy soccer players participated in a simulated soccer match that required varying intensities of intermittent exercise including 15-m sprints and soccer dribbling throughout. Blood samples were obtained before (i.e., baseline and pre-exercise) and throughout exercise (i.e., 15, 30, 45, 60, 75, 90, 105, and 120 minutes), and at half time. Sprint speeds over 15 m reduced in ET compared to the first half (−0.39 ± 0.37 m·s −1, −7 ± 6%, p = 0.021) but not the second half (−0.18 ± 0.25 m·s −1, −3 ± 4%, p = 0.086). At 105 minutes, blood lactate concentrations reduced compared with that in the opening 30 minutes (−0.9 to −1.2 mmol·L −1, p ⩽ 0.05). Blood pH (−0.03 to −0.04 units), base excess (−0.95 to −1.48 mmol·L −1 ), and bicarbonate concentrations (−0.9 ± 0.8 mmol·L −1 ) were depressed at 120 minutes compared with those at 105 minutes, baseline and half time (all p ⩽ 0.05). There were no significant correlations between changes in acid-base balance and sprint speed (all p > 0.05). Although the perturbations in acid-base balance during ET were statistically significant, the decreases in blood pH, lactate, base excess, and bicarbonate concentrations may not represent metabolic acidosis or impairments in buffering capacity that are likely to explain reduced physical performance. Further research is warranted to investigate mechanisms of fatigue during ET and to develop interventions that attenuate decrements in performance.